The Role of Notch in the Cardiovascular System: Potential Adverse Effects of Investigational Notch Inhibitors - Rizzo, Paola; Mele, Donato; Caliceti, Cristiana; Pannella, Micaela; Fortini, Cinzia; Clementz, Anthony George; Morelli, Marco Bruno; Aquila, Giorgio; Ameri, Pietro; Ferrari, Roberto (Frontiers in Oncology, 2015)
Targeting the Notch pathway is a new promising therapeutic approach for cancer patients. Inhibition of Notch is effective in the oncology setting because it causes a reduction of highly proliferative tumor cells and it inhibits survival of cancer stem cells which are considered responsible for tumor recurrence and metastasis. Additionally, since Delta- like ligand 4 (Dll4)- activated Notch signalling is a major modulator of angiogenesis, anti-Dll4 agents are being investigated to reduce vascularization of the tumor. Notch plays a major role in the heart during the development and, after birth, in response to cardiac damage. Therefore, agents used to inhibit Notch in the tumors (gamma secretase inhibitors and anti-Dll4 agents) could potentially affect myocardial repair. The past experience with trastuzumab and other tyrosine kinase inhibitors used for cancer therapy demonstrates that the possible cardiotoxicity of agents targeting shared pathways between cancer and heart and the vasculature should be considered. To date, Notch inhibition in cancer patients has resulted only in mild gastrointestinal toxicity. Little is known about the potential long term cardiotoxicity associated to Notch inhibition in cancer patients. In this review we will focus on mechanisms through which inhibition of Notch signalling could lead to cardiomyocytes and endothelial dysfunctions. These adverse effects could contrast with the benefits of therapeutic responses in cancer cells during times of increased cardiac stress and/or in the presence of cardiovascular risk factor